Pendampingan Perhitungan Potensi Penerimaan Retribusi Pelayanan Persampahan di Kabupaten Bandung - Eko Aristanto; Zaenal Aripin; Aspan Priana; Idris Idris; Vonny Novera; Diana Purnamasari; Wasinininingsih Wasinininingsih; Angga Sukmana (CV. Aksara Global Akademia, 2026)
This community engagement program aimed to assess the revenue potential of municipal solid waste service charges based on the mapping of chargeable service users and the applicable service tariffs stipulated in Bandung Regency Regional Regulation No. 9 of 2023 on Regional Taxes and Regional Charges. The strategic partners involved in this program included the Bandung Regency Environmental Agency, the Regional Technical Implementation Unit (UPTD) for Solid Waste Collection and Transportation, Integrated Waste Processing Facilities (TPST), and the Regional Final Waste Processing Site (TPPAS). The technical assistance employed a participatory approach consisting of technical coordination meetings, and field surveys to collect data, validate findings, and formulate recommendations for optimizing municipal solid waste service charge revenue. The primary outcome of this community engagement program was the successful identification of 60,341 household chargeable units and 62,635 non-household chargeable units as the basis for estimating the revenue potential of municipal solid waste service charges in Bandung Regency. Based on the assessment, the estimated revenue potential reached IDR 13,873,338,846 under the pessimistic scenario, IDR 14,500,674,306 under the moderate scenario, and IDR 18,384,609,542 under the optimistic scenario.